2021
DOI: 10.1007/s00167-021-06676-8
|View full text |Cite
|
Sign up to set email alerts
|

Seven phenotypes of varus osteoarthritic knees can be identified in the coronal plane

Abstract: Purpose Recommendations for resecting distal femur and proximal tibia in mechanical and anatomical alignment techniques are standardized. Kinematic alignment propagates individualizing resection planes. Whether significant variation exists, to warrant departure from standardized resection planes, has not been shown thus far in a large cohort of knees and with a wide range of varus deformity. The null hypothesis of this study was that there was no phenotypic variation in varus osteoarthritic knees. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…A recent study in a large series of varus osteoarthritic knees has shown an analogous classification with 7 phenotypes which could be broadly classified into 4 groups – neutral, intra‐articular varus, extra‐articular varus, and a ‘valgoid’ type [15]. The present study also has shown 4 broad phenotypes corresponding to the ones reported [15], except that the valgoid type among varus knees was replaced by ‘varus’ type for the valgus knees, and there were two additional subtypes within type 4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study in a large series of varus osteoarthritic knees has shown an analogous classification with 7 phenotypes which could be broadly classified into 4 groups – neutral, intra‐articular varus, extra‐articular varus, and a ‘valgoid’ type [15]. The present study also has shown 4 broad phenotypes corresponding to the ones reported [15], except that the valgoid type among varus knees was replaced by ‘varus’ type for the valgus knees, and there were two additional subtypes within type 4.…”
Section: Discussionmentioning
confidence: 99%
“…From the above measurements, the entire range of values of VCA were segregated into 4 groups, those of mLDFA, aLDFA and TBA into 5 groups each and TBA into 3 groups in accordance with previously reported methods [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Mullaji et al use measurement of the alignment of the lower limbs to classify KOA and explore the similarities and differences between different types. 11 However, the above researchers focused more on the influence of the anatomy of the hip or proximal femur on KOA. Other researchers have measured angles that reflect anatomic abnormalities in the hip and tried to look for correlations with changes in the alignment of lower limb.…”
Section: Introductionmentioning
confidence: 99%
“…Mullaji et al . use measurement of the alignment of the lower limbs to classify KOA and explore the similarities and differences between different types 11 . However, the above researchers focused more on the influence of the anatomy of the hip or proximal femur on KOA.…”
Section: Introductionmentioning
confidence: 99%